2013
DOI: 10.1259/dmfr.20120429
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of palatine tonsilloliths: a retrospective study on 150 consecutive CT examinations

Abstract: Palatine tonsilloliths could affect approximately one-quarter of the population. This prevalence is likely to be underestimated in daily clinical practice because small concretions do not result in any functional impairment and are not visible on orthopantomographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
5
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 9 publications
5
61
5
4
Order By: Relevance
“…In the present study on CBCT images, the prevalence of palatine tonsil calcifications was 20.4 %, which was higher than that reported by Aspestrand and Kolbenstvedt (16%) and lower than Fauroux et al (24.6%) on CT scans (16,17). …”
Section: Resultscontrasting
confidence: 79%
“…In the present study on CBCT images, the prevalence of palatine tonsil calcifications was 20.4 %, which was higher than that reported by Aspestrand and Kolbenstvedt (16%) and lower than Fauroux et al (24.6%) on CT scans (16,17). …”
Section: Resultscontrasting
confidence: 79%
“…Similar to other studies[181920] single palatine tonsillolith prevalence was lower than that of multiple ones except for the Aspestrand and Kolbenstvedt[17] study which showed the single form had higher incidence than the multiple form. CBCT images showed 18 adenoid calcifications; 14 were single and the remaining 4 were multiple.…”
Section: Discussionsupporting
confidence: 87%
“…CT scan sections had 5 mm thickness and 0–3 mm interval in Aspestrand and Kolbenstvedt[17] and 0.625–1.25 mm thickness and 0.2–1 mm interval in Fauroux et al . [18] studies. Centurion et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, it was found that the prevalence of tonsilloliths was much greater than in previous reports [1-4]. The presence of tonsilloliths may be related to halitosis based on some previous reports [5,7].…”
Section: Discussionmentioning
confidence: 79%